Influential Factors of Non-suicidal Self-Injury in an Eastern Cultural Context: A Qualitative Study From the Perspective of School Mental Health Professionals - Chen, Xiaoyu; Zhou, Ying; Li, Li; Hou, Yanfei; Liu, Ding; Yang, Xueling; Zhang, Xiaoyuan (Frontiers in Psychiatry, 2021)
Background: Adolescent non-suicidal self-injury (NSSI) is becoming a serious public health concern worldwide. There has seen a significant increase in both growth rate and cases of NSSI in eastern countries such as China in recent years. In China, most schools have a mental health office consisting of a group of mental health professions (MHPs), who are the first to respond to any student's mental health problems including NSSI. They possess deep and well-rounded knowledge as well as unique insight on the issue of adolescent NSSI. However, very few studies on NSSI have incorporated their perspectives. In this work, we seek to add new insight by carrying out a study focusing on adolescent NSSI from the perspective of school mental health professions. Methods: We recruited a total of 24 MHPs by purposive samplings from different schools and conducted a semi-structured interview regarding NSSI related issues. Each interview typically lasted about 30 minutes and is voice recorded. A thematic analysis was performed on the responses to study the most common and concerning issues behind NSSI. Results: We extracted a total of three major themes and eight sub-themes from the interview records, which included (1) the impact of Chinese culture on NSSI (gender inequality, overly high expectation, and inappropriate parenting style); (2) life event in school (internet, academic pressure, and love relationships); (3) opinions on NSSI status quo in China (ignorance and stigma). Conclusion: The results showed that culturally sensitive influential factors – gender inequality, imposed and unrealistic expectation for personal achievement, and inappropriate parenting style should be given more attention in preventing, assessing, and intervening in NSSI. Emerging factors pertaining to modern society and adolescent lifestyles such as academic pressure, internet use, and love relationships should also be carefully considered in therapy and treatment.